Tissue biochemical diversity of 20 gooseberry cultivars and the effect of ethylene supplementation on postharvest life - Anastasiadi, Maria; Mwangi, Paul M.; Ordaz-Ortiz, José Juan; Redfern, Sally P.; Berry, Mark; Simmonds, Monique S. J.; Terry, Leon A. (Elsevier, 2016)
The European gooseberry (Ribes uva-crispa) is still an understudied crop with limited data available on its biochemical profile and postharvest life. A variety of polyphenols were detected in the skin and flesh of 20 gooseberry cvs, representing mainly flavonol glycosides, anthocyanins and flavan-3-ols. In contrast, gooseberry seeds were for the first time characterised by the presence of considerable amounts of hydroxycinnamic acid glycosides tentatively identified by UPLC-QToF/MS. All cvs examined represented a good source of vitamin C while being low in sugar. Furthermore, the postharvest stability of bioactives was explored by supplementation of exogenous ethylene in air at 5 °C. Results suggest a low sensitivity of gooseberries to ethylene. The overall quality of gooseberries remained stable over two weeks, showing potential for extended bioactive life.
Keywords: Ribes uva-crispa; Ascorbic acid; QToF/MS; Ethylene; Storage; Bioactive life